Pengaruh Inflasi, Kebijakan Dividen, Profitabilitas Dan Ukuran Perusahaan Terhadap Harga Saham Pada Perusahaan Infrastruktur, Utility Dan Transportasi Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Annisa Nauli Sinaga; Stify Stify; Meliana Oktavia; Veihao Saphira (Journal of Economic, Bussines and Accounting (COSTING), 2021)
The aim this research is to know the influence of Inflation, Dividend Policy, Profitability and Company Size on Stocks Prize. This research uses a quantitive approach. The population is carried out on Infrastructure, Utility and Transportation companies that listed on the Indonesia Stock Exchange total in 74 companies. The sample of this research is 10 companies selected by purposive sampling technique. This statistical method is multiple linear regression. The results show that Dividend Policy and profitability have a positive and significant effect on stock prices. Meanwhile, Inflation and Company Size have no positive and insignificant effect on stock prices. And simultaneously Inflation, Dividend Policy, Profitability and Company Size affect the Stock Price because the value of Fcount 22.802 > Ftable 2.76. The magnitude of the coefficient of determination indicates that the stock price can be explained by the variables Inflation, Dividend Policy, Profitability, Company Size by 75%, while the remaining 25% share price is explained by other variables not examined in this research. Keywords : Inflation, Dividend Policy, Profitability, Company Size, Stocks Price